Research and Analysis of Effective Fiscal and Monetary Policy Response under the Background of International Financial Crisis - Wang, Wei; Yi, Hong (International Journal of Global Economics and Management, 2024)
In recent years, the instability and risk of the international financial market have intensified, which has made the global economy face severe challenges. The outbreak and spread of the international financial crisis have further aggravated this uncertainty. In this context, fiscal and monetary policies are considered as important tools to deal with the financial crisis. This paper aims to study effective fiscal and monetary policy responses against the background of the international financial crisis, and propose effective policy tools to deal with the negative impact of the financial crisis on the economy by analyzing the lessons learned from past financial crises and the current global economic situation.